2012
DOI: 10.7705/biomedica.v32i0.599
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory profile of Plasmodium vivax malaria patients hospitalized in Apartadó,

Abstract: Introducción. La malaria representa un problema de salud pública en la región de Urabá, donde se registran tasas superiores a las del departamento de Antioquia; la carga de malaria por Plasmodium vivax es de 78,7 % y poco se ha explorado su perfil en la región.Objetivos. Con el presente estudio se pretende conocer las características clínicas y de laboratorio de los pacientes hospitalizados por malaria por P. vivax en Apartadó.Materiales y métodos. Se revisaron las historias clínicas de pacientes con malaria p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 23 publications
(17 reference statements)
3
10
0
2
Order By: Relevance
“…Either one major or minor criterion of complication was diagnosed in P. vivax or P. falciparum cases without statistical differences, including thrombocytopenia, anemia, and liver and kidney dysfunction, consistent with other studies in Colombian patients which found liver and kidney complications and severe anemia [24]. …”
Section: Discussionsupporting
confidence: 89%
“…Either one major or minor criterion of complication was diagnosed in P. vivax or P. falciparum cases without statistical differences, including thrombocytopenia, anemia, and liver and kidney dysfunction, consistent with other studies in Colombian patients which found liver and kidney complications and severe anemia [24]. …”
Section: Discussionsupporting
confidence: 89%
“…Arboleda M et al, 4 from Colombia had reported that out of 359 patients with vivax malaria, 43 patients (12%) were suffering from severe anemia and 13 patients (3.6%) were suffering from severe thrombocytopenia.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study done in Uraba, complicated malaria due to P. vivax was estimated to be 23.1 % having severe anaemia, trombocytopenia and hyperbilirubinemia as main complications (Arboleda et al 2012). Liver failure (39.2 %) and renal failure (26.8 %) were the most frequently reported complications.…”
Section: Colombiamentioning
confidence: 92%